Regulation of Gastric Nesfatin-1/NUCB2 - Li, Ziru; Mulholland, Michael; Zhang, Weizhen (Current Pharmaceutical Design, 2013)
Originally identified in the hypothalamus as a satiety factor, recent studies provide evidence that nefatin-1/NUCB2 is a gutbrain peptide with a broader array of actions. Detection of abundant nesfatin-1/NUCB2 in gastric X/A like endocrine cells, which also produce the orexigenic hormone ghrelin, indicates that gastric mucosa may be one of the predominant sources of nesfatin-1/NUCB2. Functional studies have revealed significant effects of nefatin-1 on inhibition of feeding behavior and on glucose homeostasis. These metabolic functions make nesfatin-1/NUCB2 a novel candidate for treatment of obesity and diabetes. However, deficiencies in our understanding of nesfatin-1/NUCB2 receptor pose a significant hurdle for therapies that target its action. Defining novel pathways to alter the production of nesfatin-1/NUCB2 would shift therapeutic focus to gastric targets. A necessary precondition is improved understanding of the mechanisms by which nesfatin-1/NUCB2 is synthesized and secreted by gastric X/A like cells. Recent studies provide evidence that mTOR is a critical regulatory molecule in these endocrine cells and that its activity is linked to the production of ghrelin and nesfatin- 1/NUCB2. These findings suggest that gastric mTOR is involved in the regulation of food intake and overall energy metabolism through modulation of ghrelin and nesfatin-1/NUCB2. In this review, we first summarize current advances in the relationship between organism energy status and nesfatin-1/NUCB2 levels, and then discuss the novel finding on mTOR as the gastric fuel sensor and its role in the regulation of nesfatin-1/NUCB2 expression.
Keywords: ghrelin